PERLINDUNGAN HUKUM MEREK TERKENAL “CABERG” TERHADAP PENDAFTARAN MEREK “CABERG” LOKAL DI INDONESIA (STUDI KASUS PUTUSAN PENGADILAN NIAGA JAKARTA PUSAT NOMOR 06/Pdt.Sus-Merek/2020/ PN.Niaga.Jkt.Pst.) - Renald Saputra; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2022)
Brands have very significant benefits in encouraging the quantity of existing brands, but it cannot bedenied that there are so many brands that give rise to various conflicts and disputes that occur becauseof these various brands. In general, conflicts on brands exist due to violations of existing brands withthe motivation to get easy profits and try, or imitate, even fake brands that exist in the community. Thisstudy discusses the legal protection of the well-known brand